OP56 The cost-effectiveness of advance care planning for older adults with end-stage kidney disease. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Sellars, M; Clayton, J; Detering, K; Tong, A; Power, D; Morton, R
Abstract : Background: We aimed to examine hospital costs and outcomes of a nurse-led ACP intervention compared with usual care in the last 12 months of life for older people with end-stage kidney disease (ESKD) managed with haemodialysis. Methods: A case-control study of ACP in adults with ESKD from a major tertiary hospital and a simulation of the natural history of decedents on dialysis, using hospital data, to model the effect of ACP on end-of-life care preferences. Outcomes were assessed in terms of patients' end-of-life treatment preferences being met or not, and costs included all hospital-based care. The cost-effectiveness of ACP was assessed by calculating an incremental cost-effectiveness ratio (ICER), expressed in dollars per additional case of end-of-life preferences being met. Robustness of model results was tested through sensitivity analyses. Results: The mean cost of ACP was AUD519 per patient. The mean hospital costs of care in last 12 months of life were 100, 579 for those who received ACP versus 87, 282 for those who did not. The proportion of patients in the model who received end-of-life care according to their preferences was higher in the ACP group compared with usual care (68% vs. 24%). The incremental cost per additional case of end-of-life preferences being met was 28, 421. The greatest influence on the cost-effectiveness of ACP was the probability of dying in hospital following dialysis withdrawal, and costs of acute care. Conclusions: Our model suggests nurse-led ACP leads to receipt of patient preferences for end-of-life care, and may represent good value for money.